Inheriting Sultan Baabullah's Footsteps: Inspirational Leadership Characters for a Generation of Achievers - Rasno Ahmad; Mus S. Radjilun; Iksar Jamal (Universitas Hamzanwadi, 2026)
This research examines the paradox between the historical reverence of Sultan Baabullah as a National Hero and the lack of adequate theoretical analysis regarding the relevance of his leadership model in addressing the challenges of the 21st Century. Although his military and political achievements are widely acknowledged, the primary research gap lies in the necessity for an explicit formulation of why Baabullah's character, marked by ethical courage against foreign domination and multi-ethnic diplomacy, presents a leadership framework that is fundamentally more resilient and integrative compared to contemporary Indonesian leadership models. Employing a qualitative-interpretive approach (through historical reviews, literature analysis, and in-depth interviews), this study aims to formalize the Baabullah leadership model. This model is centered on the core values of ethical courage (integrity-based bravery) and pluralist unification (the merging of plural groups). The findings demonstrate that Baabullah's legacy constitutes a prototypical transformative leadership. He successfully aligned political authority with moral responsibility (in resisting colonialism) while simultaneously uniting ethnic and religious diversity. Theoretically, this model serves as a counter-narrative to leadership solely focused on power, emphasizing moral integrity and pluralistic competence as the foundation for sustainable leadership. The internalization of these values is expected to enrich the character education of the younger generation amidst global complexity.